Finger Millet [Eleusine coracana (L.) Gaertn]: An Orphan Crop With a Potential to Alleviate the Calcium Deficiency in the Semi-arid Tropics of Asia and Africa - Maharajan, Theivanayagam; Antony Ceasar, Stanislaus; Ajeesh Krishna, Thumadath Palayullaparambil; Ignacimuthu, Savrimuthu (Frontiers in Sustainable Food Systems, 2021)
Finger millet plays a vital role in the food and nutritional security of many people in developing countries particularly in Asia and Africa. It is a staple food for poor people in many regions of Asian (India, China, Nepal, and Sri Lanka etc.) and African (South Africa, Ethiopia, Kenya, Uganda, and Nigeria etc.) countries. Finger millet contains nutrient rich components such as dietary fibers, minerals, vitamins, and phytochemicals that include phenolic compounds with several potential health benefits. Calcium (Ca) is an important macronutrient for healthy life of plants, humans and animals. It plays an indispensable role in structure and signaling and its deficiency causes low bone density, osteoporosis, colon cancer etc. Finger millet grains contain exceptionally higher amount of Ca (>300 mg/100 g) when compared to other major cereals. Ca transporter and sensor family genes are involved in the uptake, transport and accumulation of Ca. Understanding the molecular mechanisms of Ca transporter and sensor family genes is important for growth, development and seed fortification in finger millet. Expression analysis of Ca transporter and sensor family genes has been carried out in various tissues of finger millet. Only a very little research work has been done to understand the Ca accumulation in the grains of finger millet. In this review, we discuss the nutritional importance and health benefits of finger millet. We discuss the studies on Ca sensor, accumulation and transport genes that help to improve the grains of finger millet with special reference to Ca. Improved Ca content in finger millet may help to alleviate the Ca deficiency throughout the world particularly in the semi-arid tropics of Asia and Africa.